Comparative transcriptomics reveals key regulatory networks underlying cold stress adaptation in oil palm (Elaeis guineensis) - Wu, Qiufei; Yang, Xuanwen; Huang, Qifeng; Li, Rui; Zeng, Xianhai; Li, Qihong; Li, Zongming; Fu, Dengqiang; Cao, Hongxing; Li, Xinyu; Liu, Xiaoyu; Zhou, Lixia (Frontiers in Plant Science, 2025)
IntroductionClimate change has exacerbated cold stress, which severely impairs plant development. Oil palm (Elaeis guineensis), a tropical crop highly sensitive to low temperatures, exhibits stunted growth and yield reductions under such conditions.MethodsTo investigate its cold stress response, oil palm seedlings were subjected to cold treatments, and their physiological and genetic adaptations were analyzed using fresh leaf samples. Key parameters, including antioxidant enzyme activity, reactive oxygen species (ROS) levels, photosynthetic pigment ratios, photosynthetic efficiency, and gene expression, were evaluated across exposure durations. Sequencing of the samples was performed using Illumina NovaSeq X Plus platform. Raw reads were processed using fastp (v0.18.0) to remove adapter-containing reads, exclude reads with >10% unidentified nucleotides (N), and eliminate reads where >50% of bases had Phred scores ≤20. The genome reference version is GCF_000442705.2 (https://www.ncbi.nlm.nih.gov/datasets/genome/GCF_000442705.2/).Results and discussionUnder cold stress, seedlings displayed a significant increase in superoxide dismutase (SOD, 546.08 U/g min FW) and peroxidase (POD, 153.27 U/g min FW) activities within 4 h compared with the control. Prolonged exposure (8 h) further elevated soluble sugar content (406.27 μg/g FW), malondialdehyde (MDA, 80.22 nmol/g), relative electrical conductivity (109.71%), and the carotenoid-to-chlorophyll ratio, indicating oxidative damage and membrane instability. RNA-seq analysis identified 144, 392, and 6,585 differentially expressed genes (DEGs) after 1, 4, and 8 h of cold exposure, respectively. KEGG pathway enrichment highlighted predominant associations with plant–pathogen interaction, plant hormone signal transduction, and the mitogen-activated protein kinase (MAPK) signaling pathway. Functional analysis revealed DEGs involved in four major hormone signaling pathways (auxin (AUX/IAA), jasmonic acid (JA), abscisic acid (ABA), and brassinosteroid (BR)), which also interact with the MAPK cascade to collectively regulate oil palm cold stress adaptation and growth adjustments. This study provides comprehensive insights into the genetic and molecular mechanisms underlying cold tolerance in oil palm, offering a basis for breeding cold-resistant cultivars.